Effect of less refined sugar (LRS) vs. refined sugar (RS) on postprandial glycaemic responses, glycaemic profile, and lipid profile, in normal and type 1 diabetic rats: a preliminary study - Zidan, D.; Azlan, A.; Abas, F.; Hamzah, H.; Khaza’ai, H.; Shafie, S.R.; Ebadi, S. (Universiti Putra Malaysia, 2024)
Less refined sugar (LRS) is a less refined natural sweetener that retains some polyphenols and minerals naturally occurring in the sugarcane, and its metabolic impact still needs to be studied. The present work compared the glycaemic response of three doses (Low, L; Medium, M; and High, H) of LRS and refined sugar (RS), in 54 normal and STZ-induced diabetic rats (n = 6/group). The metabolic response was also evaluated after two weeks of acute intervention in diabetic rats. The peak of glycaemia and global glucose response was lower after oral LRS administration than RS at corresponding doses, in normal and type 1 diabetic rats. After two weeks of interventions, fasting serum glucose level was found to be lower but not significant (p > 0.05) for groups receiving LRS-L, LRS-M, and LRS-H (at 11.53 ± 2.51, 12.68 ± 5.09, and 14.88 ± 1.46 mmol/L, respectively) in comparison with a corresponding dose of RS-L, RS-M, and RS-H (at 12.48 ± 0.74, 15.02 ± 1.28, and 15.70 ± 0.05 mmol/L, respectively). Consumption of LRS showed lower insulin resistance (IR), as revealed by reduced fasting insulin and homeostatic model assessment of insulin resistance (HOMA-IR) compared to RS treatment groups. This suggested that the consumption of LRS could be a less harmful alternative to RS in normal and diabetic condition, which may encourage both the industry and the public to substitute RS with LRS in food preparation and products. However, further detailed research is recommended to conclude the outcomes. © All Rights Reserved